Energy, economic and environmental analyses of a solar energy based power generation under Malaysian conditions / Md. Hosenuzzaman Abdullah - Md. Hosenuzzaman, Abdullah (2016)
Energy is the driving force for development, economic growth, automation, and modernization. Energy usage and demand are rising globally and researchers have taken this seriously to fulfill future energy demands. Solar energy is the inexhaustible and emission free energy source where the Photovoltaic (PV) is one of the most potential energy system. This research emphasizes the use of large scale PV installation as a clean energy source to support the energy demand in Malaysia. Discussion also include the 30 MW solar PV power plants and the factors that affecting power generation (cell/module types, efficiency, solar tracking system, shading, dust, life time, solar insolation and cell operating temperature), its installation cost, inverter replacement cost and land price. From the analysis, it is found that when the crystalline silicon module price is RM1.80/W (US$0.50/W), 100% self-financing and the selling price of the produced electricity is RM0.40/kWh, RM0.45/kWh, RM0.50/kWh, and 0.55/kWh, then the Net Present Value (NPV) are RM110.27 million, RM156.69 million, RM203.11 million, and RM249.53 million respectively, the Internal Rate of Return (IRR) of crystalline silicon is 6.8%, 9.2%, 11.4% and 13.5% respectively, the payback period of mono crystalline silicon is 11.4 years, 9.9 years, 8.7 years and 6.3 years respectively. When the crystalline silicon module price is RM1.80/W (US$0.50/W), 50% self-financing and 50% bank loan with 3% interest and loan tenure 15 years, the selling price of the produce electricity is RM0.40/kWh, RM0.45/kWh, RM0.50/kWh, and 0.55/kWh, then the NPV is RM18.06 million, RM16.9 million, RM50.46 million, and RM84.72 million. The IRR% is 1.6%, 4.2%, 6.6%, 8.8%, and the payback periods are 19.7 years, 16.9 years, 12.3 years, and 10.5 respectively. The grid parity is also analyzed and it is found iv that the grid parity occur within the year of 2021 to 2022 for crystalline silicon, when module price is RM1.80/W (US$0.50/W). To overcome the negative impacts of fossil fuels on the environment, many countries have been forced to change the environmental friendly alternatives energy sources. Solar energy is one of the best renewable energy sources and has the least negative impact on the environment.